2008
DOI: 10.1186/1471-2121-9-58
|View full text |Cite
|
Sign up to set email alerts
|

A role for SNX5 in the regulation of macropinocytosis

Abstract: Background: The mechanisms and components that regulate macropinocytosis are poorly understood. Here we have investigated the role of sorting nexin 5 (SNX5) in the regulation of macropinocytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 38 publications
4
69
0
1
Order By: Relevance
“…Some SNXs have also been reported to facilitate macropinosome maturation and function 23, 25, 59. Having identified SNX3 as a hit in the RNAi screen, we investigated its localization in cells that had internalized VACV MVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some SNXs have also been reported to facilitate macropinosome maturation and function 23, 25, 59. Having identified SNX3 as a hit in the RNAi screen, we investigated its localization in cells that had internalized VACV MVs.…”
Section: Discussionmentioning
confidence: 99%
“…Macropinosomes may also acquire Rab34 and early endosome antigen 1 (EEA1) needed for pinosome formation and fusion 19, 20. Acquisition of sorting nexins (SNXs) promotes tubulation to facilitate cargo recycling and macropinosome maturation 21, 22, 23, 24, 25. As they move deeper into the cytoplasm, macropinosomes acidify and acquire Rab7, Rab21 and lysosome‐associated membrane protein 1 (LAMP1) 26, 27.…”
mentioning
confidence: 99%
“…An important class of phosphoinositide effectors which regulate a variety of endocytic trafficking events, including macropinocytosis, are the sorting nexins (SNXs) (Cullen, 2008). A number of SNXs have been implicated in the biogenesis of macropinosomes, including SNX1, SNX5, SNX9, SNX18 and SNX33 (Lim et al, 2008;Wang et al, 2010). Our earlier studies have shown that SNX5 in particular is required for the early events in the formation of macropinosomes at the cell surface not only in cultured cells (Lim et al, 2008) but also primary macrophages (Lim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A number of SNXs have been implicated in the biogenesis of macropinosomes, including SNX1, SNX5, SNX9, SNX18 and SNX33 (Lim et al, 2008;Wang et al, 2010). Our earlier studies have shown that SNX5 in particular is required for the early events in the formation of macropinosomes at the cell surface not only in cultured cells (Lim et al, 2008) but also primary macrophages (Lim et al, 2012). Following EGF stimulation of HEK293 cells, SNX5 is recruited to the plasma membrane and this recruitment is dependent on phosphatidylinositol (3,4)-bisphosphate (PIP 2 ) (Lim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, macropinocytosis can also facilitate receptor-mediated signaling pathways, the entry of viral and bacterial pathogens, and cell motility (16) and is the mechanism by which macrophages and dendritic cells internalize antigens and cellular debris (16,17). More recently, macropinocytosis has also been shown to facilitate the uptake of amino acids in Ras-transformed pancreatic tumor cells to sustain their uncontrolled proliferation (14).…”
mentioning
confidence: 99%